Knowledge, awareness and attitude related to first aid among IIUM Kuantan campus students - Jamaludin, Sumaiyah @ ThandarSoe; Zakaria, Muhammad Allif (2017)
Introduction: Injuries are one of the leading causes of morbidity and mortality worldwide. Approximately, 1.25 million people lives are cut short because of road traffic crash every year. As the incidences of emergencies is steadily increasing in recent years it is important to ensure that individuals are adequately trained to deal with such events including university students. First aid is treatment for the purpose of preserving life and minimizing the consequences of injury and illness until getting help, from a medical practitioner or nurse. This study aimed to assess the level of knowledge, awareness, and attitude related to first aid among IIUM Kuantan campus students. Materials and method: A quantitative cross-sectional survey with stratified random sampling study was conducted among 348 of IIUM Kuantan undergraduate students who met the study inclusion criteria. Data were collected by using the self-administered questionnaire which was adapted from Hong Kong Red Cross. Using permission of instrument and ethical approval was obtained priority to conduction of the study. Results: Total of 316 participants had awareness and attitude towards first aid knowledge. Nevertheless, 149 participants had moderate level of first aid knowledge. There were significant associations between gender, Kulliyyah (Faculty), year of study, and first aid training experience and their level of first aid knowledge in ANOVA test with p value of 0.05. However, 55.4% of study participants did not have experienced in taking first aid course and they have little knowledge about first aid. Conclusion: Although the majority of participants had positive awareness and attitude towards first aid, their knowledge and taking first aid course were at unsatisfactory level. Therefore, there is a need of proper and regular educational programs to raise awareness in the students community about the importance of first aid practices.